Is dissolution the solution? A customer relationship reactivation model - Lopes, Luisa (2020)
Dissolution and reactivation of relationships represent the main focus of this research. Dissolution provides the context while reactivation is the explored highly complex and multifactorial phenomenon. The purpose of this study is to identify and explore the factors that lead a lost customer to accept the reactivation of the relationship. The achievement of this purpose gives a contribution not only to the scientific community but also to the economic actors that engage the option of recovering lost customers, who express an intention to abandon.